The Relationship of Physical Activity and Sleep Quality Among Elderly Who Are Still Working - Anita Tria Purnamasari; Elida Ulfiana; Andri Setya Wahyudi (Universitas Airlangga, 2021)
Introduction: The elderly tend to have short sleep duration, resulting in poor sleep quality. Physical activity is believed can improved sleep quality. This study was aimed to explain the relationship between physical activity and sleep quality among the elderly who are still working.Method: This study used a correlational research design with a cross-sectional approach. There were 63 elderly who involved as respondents by using the simple random sampling technique. The independent variable of this research was physical activities, while the dependent variable was sleep quality. A questionnaire was used to collect data. Data were then analyzed by using the Chi-Square test with a significance level of p=0.05.Results: The study found that physical activity correlates with sleep quality among the elderly who are still working (p=0.021). The elderly with moderate physical activity has three times chance to have a good sleep quality (OR=3.667).Conclusion: Moderate physical activity correlates with good sleep quality. However, an increase in physical activity will worsen the sleep quality among the elderly. The elderly who are still working can reduce the intensity of their activity in the workplace.